N6-methyladenosine RNA modification and its interaction with regulatory non-coding RNAs in colorectal cancer. (12th November 2021) - Ge, Yiling; Liu, Tong; Wang, Chuntao; Zhang, Yanqiu; Xu, Siyi; Ren, Yiyi; Feng, Yanlu; Yin, Lihong; Pu, Yuepu; Liang, Geyu
ABSTRACT: As one of the most common forms of RNA modification, N6-methyladenosine (m6A) RNA modification has attracted increasing research interest in recent years. This reversible RNA modification added a new dimension to the post-transcriptional regulation of gene expression. In colorectal cancer (CRC), the role of m6A modification has been extensively studied, not only on mRNAs but also on non-coding RNAs (ncRNAs). In the present review, we depicted the role of m6A modification in CRC, systematically elaborate the interaction between m6A modification and regulatory ncRNAs in function and mechanism. Moreover, we discussed the potential applications in clinical.